2007
DOI: 10.1038/emm.2007.15
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK and ERK activation by 9-cis-retinoic acid induces chemokine receptors CCR1 and CCR2 expression in human monocytic THP-1 cells

Abstract: 9-cis-retinoic acid (9CRA) plays an important role in the immune response; this includes cytokine production and cell migration. We have previously demonstrated that 9CRA increases expression of chemokine receptors CCR1 and CCR2 in human monocytes. To better understand how 9CRA induces CCR1 and CCR2 expression, we examined the contribution of signaling proteins in human monocytic THP-1 cells. The mRNA and surface protein up-regulation of CCR1 and CCR2 in 9CRA-stimulated cells were weakly blocked by the pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 22 publications
1
16
1
1
Order By: Relevance
“…Studies in human monocyte cell lines and epithelial cell lines find inhibition of NF B within the nucleus, possibly at the target promoters. Ko et al [36] reported in 2007 that 9cisRA in the absence of LPS induces both MAPK and ERK activation in the human monocyte cell line THP-1 peaking at 2 h. We did not observe such effects in primary monocytes in our experiments (data not shown), after the 1-hour pretreatment by 9cisRA. We did not check for further long-term effects.…”
Section: Discussioncontrasting
confidence: 39%
“…Studies in human monocyte cell lines and epithelial cell lines find inhibition of NF B within the nucleus, possibly at the target promoters. Ko et al [36] reported in 2007 that 9cisRA in the absence of LPS induces both MAPK and ERK activation in the human monocyte cell line THP-1 peaking at 2 h. We did not observe such effects in primary monocytes in our experiments (data not shown), after the 1-hour pretreatment by 9cisRA. We did not check for further long-term effects.…”
Section: Discussioncontrasting
confidence: 39%
“…The current study indicated that increases in CCR2 expression may occur via the MCPIP1 pathway. In a recent study, Jesang et al showed that p38 and Erk activation can induce CCR1 and CCR2 expression in THP-1 cells (Ko et al, 2007). To understand the signaling cascade responsible for the results of our study, we investigated the effect of SiO 2 on the MAPK and PI3K/Akt pathways.…”
Section: Discussionmentioning
confidence: 87%
“…Taken together, these studies unequivocally establish that RA synthesis occurs in the adult brain (Dev et al, 1993; Wagner et al, 2002). While most studies on RA actions are traditionally focused on its role as a transcriptional activator, various observations mostly in culture systems have demonstrated rapid transcription-independent, non-genomic RA effects that occur at the cellular periphery or at the plasma membrane (Ko et al, 2007; Masia et al, 2007; Uruno et al, 2005). Below we will discuss our recent observations on non-genomic RA actions in brain function: surprisingly, RA exerts a critical control over synaptic strength in HSP, an effect that is rapid and independent of transcription.…”
Section: Retinoid Signaling In the Adult Nervous Systemmentioning
confidence: 99%